EVALUATION OF CHRONIC PATIENT NURSING CARE BY THE PATIENTS: A UNIVERSITY HOSPITAL CASE - Akbaş, Meltem; Sürücü, Sule Gökyıldız; Akça, Emine; Köroğlu, Cemile Onat (LIFE: International Journal of Health and Life-Sciences, 2017)
This study aims to identify satisfaction levels of adult chronic patients regarding the care they received at the hospital. The descriptive and cross-sectional study was conducted at Çukurova University Faculty of Medicine Balcalı Hospital between 01.08.2016-31.10.2016. The sample consisted of 910 patients. The data was collected with “Personal Information Form” and "Patient Assessment of Chronic Illness Care (PACIC)." The data were analyzed via IBM 20.0 program. Ethical committee approval, permission from the institution and verbal consent from the patients were obtained for the study. The average age of the participants was 50.88±16.55. The average hospitalization duration was 9.22±11.55 days. It was indicated that 38% of the respondents have cardiovascular diseases, 94.6% use a kind of medication,91.7% have their medications on time, 85.5% take recommended dosages, 45.5% know the name and the number of the medication they take. The average score for chronic patient care evaluation scale was 3.11±0.74. When the subscales of the scale are analyzed, it was found that the average score for patient participation subscale is 3.75±0.93, decision-making support subscale is 3.46±3.33, target-setting subscale is 2.95±0.78, problem-solving subscale is 3.28±0.97 and monitoring/coordination subscale is 2.51±1.03. Significant correlations were found between the respondents’ education level and health education with their evaluations of chronic care. It was indicated that the patients’ satisfaction with the nursing care is medium, the highest average scores are in decision-making subscale while the average score for monitoring/coordination subscale is the lowest. In order to raise the satisfaction levels of chronic patients regarding nursing care, chronic patient care should be prioritized in organized education and on-the-job training for nurses. By emphasizing the importance of monitoring and coordinating the patients, better management of chronic diseases can be achieved.